Evaluating the management of the educational crisis in light of the Corona pandemic from the viewpoint of graduate students in Jordanian universities - Ababneh, Alaaldeen Mahmoud Mohammad (Journal of Risk and Crisis Management, 2021)
The current study aimed to reveal perceptions of graduate students to evaluate the management of the educational crisis in Jordanian public universities in the light of the Corona pandemic, and to identify the significance of the differences in perceptions of graduate students to evaluate crisis management in Jordanian universities according to the gender variable, the study was applied in the second semester 2020, and the descriptive approach was used, the study population consisted of graduate students in Jordanian public universities, and the study sample consisted of (198) male and female students. The number of male respondents was (100)، and the number of females (98) was chosen by simple random method، and the study concluded the following results: The arithmetic averages and the standard deviations of the perceptions of graduate students to evaluate the management of the educational crisis in Jordanian universities and the average as a whole ranged between (4.03-2.97) and all of them are of medium and high degrees, The overall average of the postgraduate students’ perceptions of evaluating the management of the educational crisis in Jordanian universities was (3.76) and with a high degree , There were no differences in perceptions of the respondents on the means of the tool as a whole according to the gender variable (male، female) , In light of the results, the researcher presented the following recommendations: Carrying out more studies and researches on different samples and stages , Provide adequate support to the Ministry of Higher Education and Scientific Research to assist it in achieving distance education continuously , Enhancing the partnership between public and private universities to continuously develop distance education.